Down-Regulated miR-130a/b Attenuates Rhabdomyosarcoma Proliferation via PPARG - Pan, Yi; Li, Junyang; Lou, Susu; Chen, Wanbiao; Lin, Yihang; Shen, Nan; Li, Youjin (Frontiers in Molecular Biosciences, 2022)
Background: Rhabdomyosarcoma (RMS) is one of the most common types of soft-tissue sarcomas in children, and it exhibits a low 5-years survival rate. The survival outcome has shown no significant improvements in the past 30 years miRNA profiling of RMS might therefore provide a novel insight into uncovering new molecular targets for therapy. Methods: We analyzed miRNA and RNA sequencing data from patients and the TARGET database to reveal the potential miRNA-mRNA axes and validated them in patients’ samples. After the miRNA antagomirs were used to silence the target miRNAs in the cell model, qRT-PCR, western immunoblotting analysis, and proliferation assays were performed to explore the interaction between miR-130a/b and peroxisome proliferator-activated receptor gamma (PPARG) and their effects. Results: In RMS patients, the expression of miR-130a/b was augmented, and its related PPARG gene was suppressed. Bioinformatics analysis showed that miR-130a/b targeted the PPARG gene and inhibited the proliferation of human RMS cell lines. In addition, rosiglitazone maleate activated the expression of PPARG in human RMS cell lines to suppress proliferation. Conclusion: miR-130a/b regulates the malignant process in RMS by targeting PPARG. Furthermore, the PPARG agonist rosiglitazone maleate attenuated the proliferation of RD cells and might therefore be of benefit to RMS patients.